Improving conceptual understanding of gas behavior through the use of screencasts and simulations - Brianna L. Martinez; Ryan D. Sweeder; Jessica R. VandenPlas; Deborah G. Herrington (SpringerOpen, 2021)
Abstract Background Engagement with particle-level simulations can help students visualize the motion and interactions of gas particles, thus helping them develop a more scientifically accurate mental model. Such engagement outside of class prior to formal instruction can help meet the needs of students from diverse backgrounds and provide instructors with a common experience upon which to build with further instruction. Yet, even with well-designed scaffolds, students may not attend to the most salient aspects of the simulation. In this case, a screencast where an instructor provides narrated use of the simulation and points students towards the important observations may provide additional benefits. This study, which is part of the larger ChemSims project, investigates the use of simulations and screencasts to support students' developing understanding of gas properties by examining student learning gains. Results This study indicates that both students manipulating the simulation on their own and those observing a screencast exhibited significant learning gains from pre- to post-assessment. However, students who observed the screencast were more than twice as likely to transition from a macroscopic explanation to a particle-level explanation of gas behavior in answering matched pre- and post-test questions. Eye-tracking studies indicated very similar viewing and usage patterns for both groups of students overall, including when using the simulation to answer follow-up questions. Conclusion Significant learning gains by both groups across all learning objectives indicate that either scaffolded screencast or simulation assignments can be used to support student understanding of gas particle behavior and serve as a first experience upon which to build subsequent instruction. There is some indication that the initial use of the screencast may better help students build correct mental models of gas particle behavior. Further, for this simulation, watching the instructor manipulate the simulation in the screencast allowed students to subsequently use the simulation on their own at a level comparable to those students who had manipulated the simulation on their own throughout the assignment, suggesting that the screencast students were not disadvantaged by not initially manipulating the simulation on their own.